FIRM SIZE AS A MODERATOR OF THE RELATIONSHIP BETWEEN PROFITABILITY, GREEN ACCOUNTING, CARBON EMISSION DISCLOSURE, AND FIRM VALUE - Nicholas Bintang Satria Dewa; Muslimin (Universitas Tulungagung, 2026)
This research was conducted to analyze the influence of profitability, green accounting, and carbon emission disclosure (CED) on firm value, with firm size positioned as a moderating variable. The study focused on companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. From a total population of 92 companies, 14 companies were selected as samples through a purposive sampling method, resulting in 56 observation data collected over four years. The analysis was carried out using Moderated Regression Analysis (MRA). The findings reveal that green accounting has a positive and significant impact on firm value. In contrast, profitability and carbon emission disclosure were not found to significantly affect firm value. In addition, firm size was not able to moderate the relationship between profitability, green accounting, and carbon emission disclosure on firm value, either by strengthening or weakening the effect. These results indicate that the market tends to respond more positively to companies with strong environmental accounting practices, regardless of their size, which aligns with the concepts of Legitimacy Theory and Stakeholder Theory.